Trade Policy with Increasing Returns and Imperfect Competition: Contradictory Results from Competing Assumptions. - Markusen, J; Venables, A (1988)
A number of recent papers derive different results about the effects of trade and industrial policy on imperfectly competitive industries. This paper sets out a single model within which policy under different market structures can be examined. The authors consider the four types of market structure generated by oligopoly versus free entry, and segmented markets versus integrated markets. They conclude that the effects of policy are greater when markets are segmented than when they are integrated, and that, if transport costs are small, policy is more potent when the number of firms is fixed than when there is free entry.